(untitled) (Bangladesh Journal of Pharmacology, 2023)
The study was designed to investigate the pharmacological potential of 70%methanolic extract of Vigna mungo for the management of hyperthyroidism and estrus cycle disturbances in female rats. The preliminary phytochemical analysis of the extract was performed. Hyperthyroidism was induced by administering levothyroxine (600 µg/kg; orally) for 14 days. Phytochemical analysis of the extract showed the presence of alkaloids, flavonoids, phenols, saponins, fats, and oils. The extract (300, 500, and 1,000 mg/kg; orally) and carbimazole (30 mg/kg; orally) were administered individually for the next 14 days. The extract showed dose-dependent antithyroid potential, as evidenced by the decrease in T3 and T4, and the increase in TSH levels. Body weight, body temperature, fasting blood glucose levels, and prolonged diestrus phase were reversed towards normal and significant effects on the morphology of the thyroid gland and ovary of the rats were observed. Therefore, the findings reveal that V. mungo has the potential to treat experimentally-induced hyperthyroidism and estrus cycle disturbances.